Intellectual property in the context of firms' exit strategies: The role of patents - Chahreddine Abbes; Amélie Lafrance-Cooke; Nicholas Johnston (Economic and Social Reports, 2025)
By focusing on exits, merger and acquisition and patenting activity, this paper provides a first assessment of the role of patents in firms' exit decisions. Using data from the Canadian Patent Research Database and the National Accounts Longitudinal Microdata File to track exits for cohorts of new firms, this paper explores the following questions: What is the role of patents in firms' exit decision? And more specifically: To what extent does owning patents contribute to firm survival (patent survival effect) or to exiting the market via merger and acquisition (patent trigger effect)?